Experimental Evaluation of the Shear Stress of Concrete with Macro-Synthetic Fibers and Steel Fibers for Structural - Espinoza Moreno, Jasson Hilton (2024)
This work evaluates the shear stress in concrete beams with the addition of reinforcing fibers. Since there is no established standard in Peru, it was proposed to use the "JSCE-SF6" test method recommended by the Japanese Society of Civil Engineers and an analytical model to determine the shear strength of concrete with fibers. For this purpose, steel and polypropylene fibers were used in the proportions of 3kg, 5kg, 7kg and 9kg for each design. The main test was the shear test based on Japanese standards, however, secondary tests such as compression and flexural tests were also performed. The results obtained showed the contribution of the fibers in the three tests performed. In the shear test, the polypropylene fibers obtained a higher shear strength in all their mix designs in the same proportions. Additionally, an analytical model is proposed to determine the shear stress in concrete with fibers, which includes as variables the compressive strength, the mass fraction of fibers and the tensile strength of the fibers, which generates acceptable values close to those obtained experimentally with the Japanese Standard Shear Test.